Pengaruh Kualitas Produk Terhadap Loyalitas Konsumen Pada Produk Bodylotion Scarlett Whitening (Studi Kasus Pada Mahasiswa STIE Aprin Palembang) - Hosidin; Hendra Musa (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
This research aims to determine the influence of quality Scarlett Whitening bodylotion product on consumer loyalty to STIE Aprin student in Palembang. This research is a quantitative research aimed at the relationship product quality to consumer loyalty. The sampling technique used slovin, was carried out on 100 subjects, measuring tools that used in the form of a Likert scale. The data obtained processed by simple linear regression analysis. The data was processed using SPSS 28 For Windows. The result, it was obtained that there was a positive influence significant product quality on consumer loyalty. This research is expected become input for Scarlett Whitening, the company needs to maintain quality product reliability and performance product. That consumers always have a positive attitude and commitment to continue use the product (Scarlett Whitening).